2003
DOI: 10.1016/s0308-8146(02)00498-3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative activity and total phenolic compounds of leaf, root and petiole of four accessions of Centella asiatica (L.) Urban

Abstract: Antioxidative activity and total phenolic compounds of root, leaf and petiole of four accessions of Centella asiatica (L.) Urban, namely CA 01, CA 05, CA 08 and CA 11, were evaluated. Antioxidative activity of the extracts was measured using the ferric thiocyanate (FTC) method and thiobarbituric acid (TBA) test. The antioxidative activities were then compared with that of α-tocopherol (natural antioxidant) and butylated hydroxytoulene or BHT (synthetic antioxidant). The results showed that CA 01 and CA 05 had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
174
4
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(203 citation statements)
references
References 25 publications
19
174
4
6
Order By: Relevance
“…These data are in accordance with previous research (Ao, Li, Elzaawely, Xuan, & Tawata, 2008;Liu et al 2008;Zainol, Abd-Hamid, Yusof, & Muse, 2003), which has shown that a high total polyphenol content increases antioxidant activity and that a linear correlation exists between the phenolic content and antioxidant activity. Ao et al, (2008) also reported that the correlation coefficient between antioxidant activity and polyphenols was higher when the method used for determining this antioxidant activity was the ABTS assay rather than other methods (1,1-diphenyl-2-picrylhydrazyil radical scavenging assay, phenazine methosulfate-nicotinamide adenine dinucleotidereduced system superoxide-radical scavenging assay, or b-carotene/linoleic acid system antioxidant assay).…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…These data are in accordance with previous research (Ao, Li, Elzaawely, Xuan, & Tawata, 2008;Liu et al 2008;Zainol, Abd-Hamid, Yusof, & Muse, 2003), which has shown that a high total polyphenol content increases antioxidant activity and that a linear correlation exists between the phenolic content and antioxidant activity. Ao et al, (2008) also reported that the correlation coefficient between antioxidant activity and polyphenols was higher when the method used for determining this antioxidant activity was the ABTS assay rather than other methods (1,1-diphenyl-2-picrylhydrazyil radical scavenging assay, phenazine methosulfate-nicotinamide adenine dinucleotidereduced system superoxide-radical scavenging assay, or b-carotene/linoleic acid system antioxidant assay).…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…These compounds have significant application against human pathogens, including those that cause enteric infections and are reported to have curative properties against several pathogens and therefore could suggest their use in the treatment of various diseases (Hassan et al, 2004). In general, the total phenolic compounds found in the leaf, root and petiole are the major contributions to the antioxidant activities of the plant (Zainol et al, 2003). Saponin is not detected in C. asiatica in the present study, whereas alkaloids are present in all the tested extracts.…”
Section: Resultscontrasting
confidence: 55%
“…This finding provides evidence that tissues of grapevine seedlings subjected to stress contain less antioxidants and reducing compounds. Zainol et al (2003) showed that the phenolic compounds are the major contributors to the antioxidative activities. The extent of antioxidative effects produced by phenols largely depends on the structure of given compound and especially on the number and distribution of hydroxyl groups (-OH).…”
Section: Discussionmentioning
confidence: 99%